SISTEM PENDUKUNG KEPUTUSAN PENENTUAN ANGGOTA TERBAIK PADA BAITUL MAAL WA TANWIL KABANDUNGAN DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Annisa Auralia (2022)
The position of members in sharia cooperatives such as Baitul Maal wa Tanwil (BMT) is very important, because BMT cannot run without members. It should be noted that currently BMT Kabandungan has around 3,500 members. However, not all of these members participate actively. Therefore, to encourage activeness and maintain members of BMT Kabandungan, a determination of the best members is held every year where the best members will get privileges from BMT Kabandungan. BMT Kabandungan must be careful in determining the best members, so a decision support system is needed to assist BMT Kabandungan in conducting the member assessment process. The method applied in this decision support system is the Simple Additive Weighting (SAW) because this method can provide the best alternative and in accordance with predetermined criteria. The criteria used in this decision support system are the amount of savings, the number of transactions and the amount of profit generated. In making this system using the stages of the Waterfall model and the PHP programming language and MySQL database. The final result of this research has successfully built a decision support system to determine the best members according to the needs of BMT Kabandungan. Keywords: Decission Support System, Simple Additive Weighting, Best Member